Aesthetics and politics - Adorno, Theodor (Radical thinkers ;, 2007)
In 'Aesthetics and Politics' the key texts of the great Marxist controversies over literature and art are assembled in a single volume. They do not form a disparate collection but a continuous, interlinked debate between thinkers who have become giants of twentieth-century intellectual history.